2020
DOI: 10.1016/j.infsof.2020.106279
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Java software similarities by using different clustering techniques

Abstract: Background-Research on empirical software engineering has increasingly been conducted by analysing and measuring vast amounts of software systems. Hundreds, thousands and even millions of systems have been (and are) considered by researchers, and often within the same study, in order to test theories, demonstrate approaches or run prediction models. A much less investigated aspect is whether the collected metrics might be context-specific, or whether systems should be better analysed in clusters. Objective-The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 75 publications
0
4
0
1
Order By: Relevance
“…However, their work is limited by the external library call which may fool as the similarity will largely depends on it. Another study [33] has confirmed that CrossSim may identify dissimilarity based on external API usage while internally implementing similar functionalities.…”
Section: Related Workmentioning
confidence: 84%
“…However, their work is limited by the external library call which may fool as the similarity will largely depends on it. Another study [33] has confirmed that CrossSim may identify dissimilarity based on external API usage while internally implementing similar functionalities.…”
Section: Related Workmentioning
confidence: 84%
“…To conduct the comparison with PAM, we exploited its original source code which has been made available online by its authors. 7 Furthermore, to facilitate future replications, we published all the artifacts together with the tools used in our evaluation in GITHUB [27].…”
Section: Discussionmentioning
confidence: 99%
“…This essentially means that these categories do not have much to do with similarity in API usages. Recently, attempts have been made to automatically assign a category to projects/apps [7], [43]. Among others, supervised learning techniques perform computation by exploiting labeled data, e.g., the apps and their corresponding categories specified by developers.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…A study conducted by [38] stated that the cluster sampling technique is applied to get a sample from Java software that consists of a similar system and to display the differences between the clusters. The software is grouping into the cluster using the CrossSim algorithm to observe the similarities.…”
Section: ) Cluster Samplingmentioning
confidence: 99%